Catalytic Enantioselective CH Functionalization of Alcohols by Redox‐Triggered Carbonyl Addition: Borrowing Hydrogen, Returning Carbon. Issue 35 (23rd July 2014) - Ketcham, John M.; Shin, Inji; Montgomery, T. Patrick; Krische, Michael J.
Abstract The use of alcohols and unsaturated reactants for the redox‐triggered generation of nucleophile–electrophile pairs represents a broad, new approach to carbonyl addition chemistry. Discrete redox manipulations that are often required for the generation of carbonyl electrophiles and premetalated carbon‐centered nucleophiles are thus avoided. Based on this concept, a broad, new family of enantioselective CC coupling reactions that are catalyzed by iridium or ruthenium complexes have been developed, which are summarized in this Minireview.